Diverse novel solutions for the ionic current using the microtubule equation based on two recent computational schemes - Khater, Mostafa M. A.; Lu, Dianchen; İnç, Mustafa (Springer, 2021)
The accuracy of computational solutions for the ionic current obtained using the microtubule (MTU) equation is analyzed. The MTU equation has various applications for the ionic current in biological non-linear dispatch line and can be used to describe the ionic transport throughout the intracellular environment. The extended simple equation (ESE) and generalized exp (-phi(xi) expansion (GEE) schemes result in many distinct solutions. The aim of this work is to investigate the accuracy of these solutions and thereby the applied computational schemes. The process depends on extracting the initial and boundary conditions from the obtained analytical solutions followed by the application of the well-known Adomian decomposition (AD) and homotopy perturbation (HP) methods. Microtubules are one of the main components of the cytoskeleton, carrying out many operations including intracellular transmit, and DNA division, intracellular transmission, and DNA division, thereby motivating their study using the described model. The results demonstrate that the proposed methods are very powerful, innovative, facile, suitable, and convenient for solving many such nonlinear models.
Keywords: Ionic current; Microtubule equation; Semianalytical solutions; Accuracy of computational solutions